Socialization and Assistance in Creating a Business Identification Number (NIB) and Halal Certification for Micro Business Actors in Mendalo Darat Village, Muaro Jambi Regency: Sosialisasi dan Pendampingan Pembuatan Nomor Induk Berusaha (NIB) dan Sertifikasi Halal bagi Pelaku Usaha Mikro di Desa Mendalo Darat Kabupaten Muaro Jambi - Siti Marlina; Ghina Nazwha Nazara; Mona Lisa; Nabella Laras Shati; Ratmi Indah Eka Safitri; Rendy Angga Syaputra Siregar (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Business legality is a crucial foundation for MSME development, both in terms of access to capital, participation in government programs, and consumer trust. However, many MSMEs in rural areas still lack a Business Identification Number (NIB) and are unfamiliar with halal certification procedures. This community service activity was carried out by students from UIN STS Jambi through the Independent Community Service Program (KKN Mandiri), focusing on providing direct assistance to MSMEs in Mendalo Darat Village, Muaro Jambi Regency. The activity was conducted through a door-to-door approach to reach business owners personally. The results of this activity showed that of the 135 MSMEs recorded, 40 successfully obtained a NIB, and several others have begun the halal certification process. This activity is a real contribution to supporting local economic empowerment and increasing business legality literacy in the community